2018
DOI: 10.1016/j.pec.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing women’s decision making in hysterectomy

Abstract: Additional information, or education about avoiding open abdominal approach where possible may lead to a greater number of women receiving less-invasive types of hysterectomy in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Previous studies examined the relationships between surgical approach to hysterectomy and women’s quality of life, for both benign and oncologic conditions ( 14 19 ). Most studies compared laparoscopic and open abdominal surgery ( 9 – 13 ), while 1 study compared TLH, VH, and TAH ( 8 ), and 4 TLH versus RH, reviewed in Albright et al ( 20 ). These studies all concluded that minimally invasive surgical approaches were associated with better postoperative quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies examined the relationships between surgical approach to hysterectomy and women’s quality of life, for both benign and oncologic conditions ( 14 19 ). Most studies compared laparoscopic and open abdominal surgery ( 9 – 13 ), while 1 study compared TLH, VH, and TAH ( 8 ), and 4 TLH versus RH, reviewed in Albright et al ( 20 ). These studies all concluded that minimally invasive surgical approaches were associated with better postoperative quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Among 285 Australian obstetrics and gynecology specialists, the dominating barrier to practicing less invasive surgery was a lack of surgical training and mentoring (9). Among women who had a hysterectomy in the previous 2 years, the majority (62%) followed their doctor's advice on the surgical approach, and very few (<15%) sought a second opinion (10).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly likely to affect surgeons in smaller, rural hospitals where a lack of training opportunities will limit the number of surgeons performing MAS procedures 5. Low numbers of patients requesting MAS may also limit uptake, either because patients are unaware of MAS or that the technique is associated with improved outcomes 5 9…”
Section: Introductionmentioning
confidence: 99%
“…To investigate why TAH was still commonly used, a survey of Australian and New Zealand gynaecologists identified two main barriers impeding the uptake of TLH: (1) surgeons’ lack of procedural skills for TLH and (2) the limited availability of structured training and mentoring opportunities to assist practising surgeons to gain those skills 27. Women who have had a hysterectomy were surveyed and reported that they commonly follow the advice of their doctor with regards to the type of hysterectomy, and rarely reported to seek a second opinion 28…”
Section: Rationalementioning
confidence: 99%